2007
DOI: 10.1111/j.1523-5378.2007.00478.x
|View full text |Cite
|
Sign up to set email alerts
|

The Current Status of Helicobacter pylori Vaccines: A Review

Abstract: Helicobacter pylori, a Gram-negative flagellate bacterium that infects the stomach of more than half of the global population, is regarded as the leading cause of chronic gastritis, peptic ulcer disease, and even gastric adenocarcinoma in some individuals. Although the bacterium induces strong humoral and cellular immune responses, it can persist in the host for decades. It has several virulence factors, some of them having vaccine potential as judged by immunoproteomic analysis. A few vaccination studies invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 151 publications
2
38
0
1
Order By: Relevance
“…The present study results showed insignificant correlation between age and H. pylori antibodies, this was similar to study done in Iran by Alavi and others in 2010 [24], but it differ from Kabir, (2007) in Sweden who reported that the percentage of infected people increase with age [25]. Also Forman and Burley in 2006, stated that the prevalence of H. pylori infections increase, with age [26].…”
Section: Discussionsupporting
confidence: 87%
“…The present study results showed insignificant correlation between age and H. pylori antibodies, this was similar to study done in Iran by Alavi and others in 2010 [24], but it differ from Kabir, (2007) in Sweden who reported that the percentage of infected people increase with age [25]. Also Forman and Burley in 2006, stated that the prevalence of H. pylori infections increase, with age [26].…”
Section: Discussionsupporting
confidence: 87%
“…One such therapeutic effect is the reversal of methylation of E-cadherin induced by H. pylori in the stomach, and consequently reduction in the risk of cancer development [96,97]. A further option would be vaccines against the bacterial strain in question, such as investigated again for H. pylori [98], but not clinically effective as yet.…”
Section: Potential Therapeutic Implicationsmentioning
confidence: 97%
“…However, since it is possible to elicit protective immunity in mice that lack B cells (53, 137) and since H. pylori infection is not cleared in humans without antibiotic intervention, the humoral immune response has been considered to be an indication of infection, rather than a marker of protection (72). Furthermore, on the basis of evidence obtained using a B cell-deficient mouse model, H. pylorispecific antibodies may actually enhance colonization (3,72).…”
Section: Adaptive Immune Responsementioning
confidence: 99%
“…H. pylori has a series of mechanisms that enable it to evade cell-mediated and cell-free immune killing. While the bacterium has been shown to be efficiently coated by antibodies in vitro and in vivo (72,141), H. pylori also avoids antibody-dependent cell-mediated cytotoxicity, complement fixation, and the agglutinating effects of antibodies. Furthermore, the effector cells recruited to the site of infection are unable to clear the bacterium by the array of antioxidant compounds that can be deployed by H. pylori and by disturbed phagosome maturation.…”
Section: How H Pylori Circumvents Phagocytic Killingmentioning
confidence: 99%